The analysis of Employment Quality of Chinese Vocational and College Graduates - Yang, Po; Guo, Jianru; Jin, Yinan; Education, School Of; University, Peking (Research in Educational Development, 2013)
College graduate's employment quality is one of the most heatedly discussed issues recently. Giving the difference in purposes of talent cultivation in academic and vocational institutions and the difference in individual job-searching strategy, this paper proposes that scholars should compare the difference of job-searching strategy and the gap in actual employment outcome between academic and vocational college graduates and analyze the level of compatibility between vocational graduate's job-searching strategy and their job-searching result, in order to identify the effect of vocational higher education on employment. Using the proposed method, this study finds a great gap in job-hunting strategy among two types of graduates. Vocational higher education significantly affects one's job-hunting strategy and employment result. Besides, vocational graduate's job-hunting strategy indeed influences their employment outcomes. In conclusion, this paper believes that vocational graduates' employment quality is not necessarily worse than that of academic graduates.
Keywords: job-hunting strategy; employment quality; vocational higher education